The Effect of Economic Growth and Poverty on Development Disparities in West Java Province - Dyah Poespita Ernawati (Budapest International Research and Critics University, 2021)
The purpose of this study is to ascertain the influence of economic growth on development inequalities in West Java Province and on employment in the province. The data utilized in this study are secondary data from the Central Statistics Agency (BPS) from 2010 to 2019. The descriptive and multiple linear regression analyses were employed in this study.Ṫhe results showed that the development disparity in West Java was high, as indicated by the Williamson index between 0.61 and 0.70. This study also found that economic growth partially and simultaneously had no significant effect on development disparities in West Java, and poverty also partly and simultaneously did not significantly affect development disparities in West Java.